Sharing Knowledge: Utilizing Cape Gooseberry Fruit to Reduce the Risk of Hypertension in Pregnant Women - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
One of the frequently encountered health issues, particularly among pregnant women, is hypertension. Hypertension during pregnancy poses a serious risk to the health of both the pregnant woman and the fetus. This issue requires special attention, especially in providing information to the public about alternative approaches to managing blood pressure. To address this problem, an educational campaign on the benefits of cape gooseberry for hypertensive pregnant women was conducted. Cape gooseberry, scientifically known as Physalis angulata, holds the potential in helping to reduce blood pressure in hypertensive individuals. Compounds found within the cape gooseberry, such as flavonoids and polyphenols, possess anti-hypertensive properties that could benefit health. Several studies indicate that cape gooseberry can lower blood pressure. The Community Engagement Activity (PKM) was held in Lau Rakit Village, STM. Hilir Sub-district, Deli Serdang Regency, on November 29th, 2023, involving 15 participants. The primary aim of this PKM is to enhance public knowledge, particularly among hypertensive pregnant women, regarding the benefits of cape gooseberry in reducing blood pressure and the appropriate methods of consumption. Additionally, this activity aims to raise awareness about the significance of nutrition in maintaining health during pregnancy. The educational campaign succeeded in increasing public knowledge about the benefits of cape gooseberry in reducing blood pressure. Positive responses were evident through active participation among the community in seeking further information regarding cape gooseberry and its consumption. It is anticipated that this educational campaign will serve as a foundation in the endeavor to manage community health, particularly concerning hypertension during pregnancy.